2015
DOI: 10.1007/s00442-015-3449-5
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive response to nitrogen and phosphorus fertilization along the Hawaiian archipelago’s natural soil fertility gradient

Abstract: Nitrogen (N) and phosphorus (P) are the most important nutrients involved in plant reproduction and typically the most limiting in terrestrial ecosystems. The natural soil fertility gradient of the Hawaiian archipelago, in which younger islands are N limited and older islands are P limited, provides a model system to examine questions regarding allocation of nutrients. Using fertilized plots (+N or +P) at the extreme sites of the Hawaiian archipelago, vegetative productivity (e.g., net primary productivity, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…As the quantity and quality of seeds are indicators of how the plant allocates resources according to nutrient availability in soil (Sinclair & Vadez ; Hulshof et al . ; Marschner ; DiManno & Ostertag ), our results strongly suggest that nurses living with their facilitated plants have greater access to resources via mycorrhiza. Similarly, fungicide could be negatively affecting the facilitated plants because the reduction of their extra‐radical mycelia decreases the volume of soil to explore and disrupts the connections with M. luisana through which N is received (Montesinos‐Navarro et al .…”
Section: Discussionsupporting
confidence: 56%
“…As the quantity and quality of seeds are indicators of how the plant allocates resources according to nutrient availability in soil (Sinclair & Vadez ; Hulshof et al . ; Marschner ; DiManno & Ostertag ), our results strongly suggest that nurses living with their facilitated plants have greater access to resources via mycorrhiza. Similarly, fungicide could be negatively affecting the facilitated plants because the reduction of their extra‐radical mycelia decreases the volume of soil to explore and disrupts the connections with M. luisana through which N is received (Montesinos‐Navarro et al .…”
Section: Discussionsupporting
confidence: 56%
“…This may be because tree species on P-poor soils accumulate P in seeds (DiManno & Ostertag 2016, Witkowski 1990). The accumulation of P in seeds was often found in species naturally growing on P-poor soils (Atkinson & Davison 1971, DiManno & Ostertag 2016, Groom & Lamont 2010, Witkowski 1990). For instance, DiManno & Ostertag (2016) conducted P or N fertilization experiments at two sites with contrasting soil fertility (P-limited sites vs. N-limited sites) in the Hawaiian Archipelago, and found that Metrosideros polymorpha (Myrtaceae) at the P-limited sites accumulated P in seeds in response to P fertilization while that at the N-limited sites did not.…”
Section: Discussionmentioning
confidence: 99%
“…Groom & Lamont (2010) showed that Proteaceae from south-western Australia (stronger P deficiency) had on average a two-fold greater P concentration in seeds than those from the Cape of Africa (weaker P deficiency). The accumulation of P in seeds is considered to be an adaptive mechanism to P deficiency (DiManno & Ostertag 2016, Lambers et al 2015), because the storage of P in seeds contributes to rapid seedling growth on P-poor soils (Groom & Lamont 2010, Thomson & Bolger 1993, Vandamme et al 2016). Exceptionally, P concentration in the seeds of Syzygium species significantly decreased with decreasing soil P availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of each environmental characteristic to changes in plant traits, animal assemblages and microbial communities with increasing altitude (Figure 1) cannot easily be separated. However, the trend for smaller trees, lower diversity of fleshy-fruited tree species and smaller crop size can be directly linked to soil nutrient availability, especially nitrogen (N), which is critical for fruit production (DiManno & Ostertag 2016). Nitrogen often declines, or become less available to plants (Carbutt et al 2013) with increasing altitude, and this, together with fewer beneficial soil micro-organisms in TMF in general (Dalling et al 2016, Tanner et al 1998), leads to trade-offs in plant functional traits.…”
Section: Changes With Altitudementioning
confidence: 99%